TRADISI BURDE’EN DALAM MENANGANI COVID-19 DI DUSUN SAPA’AH DESA KOMBANGAN - Ummu Kulsum, Roudlotul Jannah; Moh. Abdulloh Hilmi (DIRAYAH : Jurnal Ilmu Hadis, 2022)
Burde'en (recitation of salawat burdah around the hamlet every night) which was initiated by religious elites (ustaz, kiai) in Sapa'ah Hamlet, Bangkalan, Madura was carried out to deal with Covid-19. The implementation of this tradition is contrary to the provisions of the government's health protocol which is based on a medical approach even though it appears with the same goal: eradicating Covid-19. In fact, this tradition actually triggers crowds, not wearing masks, and so on. So, the question to be answered in this study is: "How do people interpret the burde'en tradition so that it is chosen as a way to deal with Covid-19?" In answering this question, the approach used is Phenomenology by adopting the functional theory of Thomas F. O'dea, to provide a clear explanation of the meaning of what is called religious behavior. As a result, this study shows that, there are three aspects that influence people to choose the burde'en tradition. First, the agency system, namely the existence of the clerical elite itself which is believed to be authoritative because it has cultural capital, including being believed to be authoritative in talking about Covid-19. Second, religious ideology which tends to be theological; In this case, Covid-19 is positioned as a disease brought by demons/jinns so that its handling must be based on religious texts that are considered legitimate (salawat burdah). Third, uncontrolled social media reporting, and often creating hoax news related to the handling of Covid-19 patients, which usually ends in death; This in turn eliminates public trust in state institutions.